Critical Comparison of Muhammad Syahrur and Fazlur Rahman's Thoughts on Inheritance Law: Modern Reconstruction of the Principles of Justice in Islam - Arifin, Muhamad Zaenal (IJoIS: Indonesian Journal of Islamic Studies, 2024)
The discourse on Islamic inheritance law continues to evolve amid contemporary social and economic changes. This study aims to compare Muhammad Syahrur's theory of limits (nazariyyah al-hudud) and Fazlur Rahman's double movement approach in understanding Islamic inheritance law, assessing their relevance and applicability in the modern context. This research employs a qualitative method with descriptive-analytical and comparative analysis approaches. Data were gathered through literature reviews of the primary works of both scholars and supporting literature. The findings reveal that Syahrur's approach provides flexibility that allows law to adapt to social changes, while Rahman emphasizes the importance of linking the historical context of the Qur'an to modern conditions. Both approaches have strengths and potential for integration to create an adaptive, relevant, and justice-aligned legal framework in Islamic jurisprudence. The study's implications point towards policy recommendations for more inclusive and responsive Islamic inheritance laws.